2016
DOI: 10.3168/jds.2015-10580
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukemia virus infection in cattle of China: Association with reduced milk production and increased somatic cell score

Abstract: The main objective of this study was to investigate the individual cow effect of bovine leukemia virus (BLV) infection on milk production and somatic cell score (SCS). The fluorescence resonance energy transfer (FRET) quantitative PCR established in this study and a commercial ELISA kit revealed that 49.1% of dairy cattle (964/1,963) from 6 provinces of China and 1.6% of beef cattle (22/1,390) from 15 provinces were BLV positive. In a detailed study of 105 cows, BLV was found most commonly in buffy coat sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 21 publications
10
68
0
4
Order By: Relevance
“…In the US, where there is no control program for BLV, the animal-level prevalence in the dairy cattle population has increased steadily from approximately 10% at that time to over 40% today [5–12]. Other major dairy producing countries that have not implemented large-scale eradication programs, including Canada, Argentina, Japan, and China, have also reported BLV prevalence in their dairy herds of 30-50% [11, 1321]. In contrast, 19 member states of the European Union, the United Kingdom, New Zealand, and Australia have completely eradicated BLV from their dairy cow populations, and control programs are underway in the remaining member states of the EU resulting in an overall herd prevalence in the EU of less than one percent [11, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, where there is no control program for BLV, the animal-level prevalence in the dairy cattle population has increased steadily from approximately 10% at that time to over 40% today [5–12]. Other major dairy producing countries that have not implemented large-scale eradication programs, including Canada, Argentina, Japan, and China, have also reported BLV prevalence in their dairy herds of 30-50% [11, 1321]. In contrast, 19 member states of the European Union, the United Kingdom, New Zealand, and Australia have completely eradicated BLV from their dairy cow populations, and control programs are underway in the remaining member states of the EU resulting in an overall herd prevalence in the EU of less than one percent [11, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…While some previous studies do not show significant negative effects of BLV infection on production and longevity or survival [13, 24, 25], the majority of recent studies have reported a negative association between BLV infection and both milk production and cow longevity [21, 22, 2632]. Between 2010 and 2012, our research group conducted studies of BLV in 113 Michigan dairy herds using milk ELISA1 testing of a sample of 40 cows in each herd to estimate within-herd AP, which ranged from 0% to 80.6% with an average of 32.8% [9, 3336].…”
Section: Introductionmentioning
confidence: 99%
“…62 This increase of SCC may indicate that BLV-infected cattle could present higher incidence of mastitis than BLV-free animals. A high SCC in milk is undesirable for the dairy industry because it increases the acidity of milk and decreases the quality of cheese.…”
mentioning
confidence: 99%
“…BLV-infected cows with ≥4 parities in their early and middle lactation stage had 13.2% and 14.9% reduction rate, respectively, compared with noninfected cows. 62 Another study analyzed the lactation history and BLV infection status of 4,052 cows from 348 herds and showed that infected cows in their 2nd and 3rd lactations had significantly lower life milk production compared with their negative counterparts with the same number of lactations. No significant differences were found between infected and noninfected cows with >3 lactations.…”
mentioning
confidence: 99%
“…The BLV FRET-PCR was performed as described previously [3] in a LightCycler 480 II real-time PCR platform to detect BLV. In brief, the gag gene sequences of representative BLV isolates were obtained from GenBank and the Clustal multiple alignment algorithm was used to identify a highly conserved region of the proviral polymerase DNA gene common to all the above BLV gene sequences.…”
Section: Methodsmentioning
confidence: 99%